THE EFFECTIVENESS OF CLUSTERING AND FREEWRITING AS PREWRITING ACTIVITY FOR STUDENT’S WRITING ABILITY IN IKIP BUDI UTOMO MALANG - Ike Dian Puspita Sari (IKIP Budi Utomo Malang, 2017)
Writing is productive skill which demands students to think logically. In this research, the researcher used two groups consisting Group A (20 students) who was given clustering as prewriting activity, and Group B (20 students) who was given freewriting as their prewriting activity. The result shows that clustering which was used by Group A did not show significant effect toward students’ writing ability. While, freewriting which is used in Group B shows significant effect towards students’ writing ability. The two different results found might be caused by grammatical and vocabulary items scores in students writing draft